Determining optimal Mid-Upper Arm Circumference (MUAC) cutoffs maximizing admission of wasted children to treatment in the Philippines - Lyle Casas; Jhanna Uy; Eldridge Ferrer; Charmaine A. Duante; Paluku Bahwere; Rene Gerard Galera; Alice Nkoroi; Mueni Mutunga; Sanele Nkomani; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2025)
In low resource settings where it is challenging to obtain accurate weight-for-height Z-scores (e.g., equipment to accurately measure height and weight is not readily available, minimally trained community health workers, etc.), the Mid-Upper Arm Circumference (MUAC) is a simple tool used to identify wasted children. However, some researchers and practitioners argue that relying solely on MUAC may miss identification of many wasted children, leading to untimely intervention and potentially death. Our study aimed to identify the best-performing MUAC cutoffs to accurately detect wasting by Weight-for-Height z-scores (WHZ) in Filipino children aged 6-59 months. We analyzed the 2018-2019 Expanded National Nutrition Survey (ENNS) to assess the diagnostic performance of MUAC cutoffs in identifying moderate and severe wasting. The optimal cutoff is identified as the cutoff having the highest AUROC curve. Our findings suggest that the current MUAC cutoffs showed poor performance in identifying severe (sensitivity: 13%; specificity: 99%; AUROC: 0.558) and moderate (Sensitivity: 22%; Specificity: 96%; AUROC: 0.0586) wasting. The optimal MUAC cutoff to optimize the identification of severe and moderate wasting was <13.6cm (sensitivity: 62%; specificity: 76%; AUROC: 0.690) and 14.0cm (sensitivity: 80%; specificity: 67%; AUROC: 0.737), respectively. While there was almost no effect of the gender on optimal MUAC cutoff, but it increased with age. We found that the combination of WAZ < -2 or MUAC È 12.7cm (Sensitivity: 84%; Specificity: 78%; AUROC: 0.810) for moderate wasting and WAZ < -2 or MUAC È 11.7cm (Sensitivity: 80%; Specificity: 80%; AUROC: 0.800) for severe wasting were the optimal criteria. These cutoffs exhibited vastly improved diagnostic sensitivity at the cost of acceptable decreases in specificity. Our results are intended to contribute to local and global evidence to further refine the identification and management of acute malnutrition, improving access and coverage for the Philippine Integrated Management of Acute Malnutrition (PIMAM) services. These include the consideration of alternative case definitions (incorporating WAZ with MUAC) in the diagnostic criteria for wasting in contexts where the WHZ indicator cannot be used. Further implementation studies, however, is recommended to validate findings and better understand its practical use and cost to the health system are vital to implementing changes effectively and sustainably in identifying and treating acute malnutrition in the Philippines.
Keywords: 330; wasting; mid-upper arm circumference; weight-for-age; weight-for-height; Philippines